Для гомогенізації молока - Ромоданова, Валентина Олександрівна; Кочубей-Литвиненко, Оксана Валер'янівна; Шурчкова, Юлія Олександрівна (My University, 1998)
Наведено опис та порівняльні технічні характеристики вакуумного гомогенізатора, розробленого в Інституті технічної теплофізики НАН України, в порівнянні з деякими найбільш розповсюдженими гомогенізаторами клапанного типу. Доведений позитивний технологічний та економічний ефект від впровадження вакуумного гомогенізатора у технологію згущеного молока з цукром. A description and comparative characteristics of vacuum homogenizer, developed at the Institute of Engineering Thermophysics, NAS of Ukraine, compared to some of the most common type homogenizer valve. Described the impact on vacuum homogenizing milk mixture and sweetened condensed milk, and milk is increasing thermal stability, reduced titrated acidity, preventing the formation of aggregates of fat globules and advocacy fat, reducing the number of pathogenic organisms and, as a result, increase the shelf life of canned condensed. Proven positive technological and economic impact of the introduction of technology in vacuum homogenizer condensed milk with sugar.
Keywords: згущене молоко з цукром; молочна суміш; гомогенізація; sweetened condensed milk; milk; milk formula; homogenization; кафедра технології молока і молочних продуктів